2019
DOI: 10.1002/bimj.201800250
|View full text |Cite
|
Sign up to set email alerts
|

A multistate model for early decision‐making in oncology

Abstract: The development of oncology drugs progresses through multiple phases, where after each phase, a decision is made about whether to move a molecule forward. Early phase efficacy decisions are often made on the basis of single-arm studies based on a set of rules to define whether the tumor improves ("responds"), remains stable, or progresses (response evaluation criteria in solid tumors [RECIST]). These decision rules are implicitly assuming some form of surrogacy between tumor response and long-term endpoints li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“… 39 Moreover, when patients are allowed to switch to secondary therapies, regardless of whether secondary therapies consisting of drugs are from the same class 40 or a chemotherapy cocktail, the traditional survival analysis becomes weaker to identify any treatment benefit of the new treatment. Beyer et al 12 demonstrated the application of multistate models in oncology trials. Furthermore, the multistate model can be used to predict the probability of intermediate events (states) for a future clinical trial population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 Moreover, when patients are allowed to switch to secondary therapies, regardless of whether secondary therapies consisting of drugs are from the same class 40 or a chemotherapy cocktail, the traditional survival analysis becomes weaker to identify any treatment benefit of the new treatment. Beyer et al 12 demonstrated the application of multistate models in oncology trials. Furthermore, the multistate model can be used to predict the probability of intermediate events (states) for a future clinical trial population.…”
Section: Discussionmentioning
confidence: 99%
“…Multistate models have been recommended and has been increasingly used for such data. 9 , 10 , 11 For the analysis of survival data, Beyer et al 12 developed a multistate model, where the transition hazards of intermediate events were modeled using semiparametric models with a treatment arm as a binary covariate. The implementation of multistate models in a nonlinear mixed effect (NLME) modeling framework would allow NLME‐derived covariate evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects rather the practical restrictions in observing the data than the true mechanism of action. Alternatively, a multistate model 24 could be considered: initial state would be “SD and alive”, the final state would be “death”. There are also two intermediate states “CR/PR” and “PD,” which lead to different hazards of death.…”
Section: Discussionmentioning
confidence: 99%
“…These hazards for “CR/PR” and “PD” could be chosen in a way that expected response rates at t 0 are reflected. Such an approach was recently implemented 24 …”
Section: Discussionmentioning
confidence: 99%
“…Different extensions of this model have been introduced in the literature [8][9][10][11]. Dynamic models based in the Cox one are Reference [12][13][14][15], among others.…”
Section: Introductionmentioning
confidence: 99%